Experimental study of liposomal docetaxel analysis of docetaxel incorporation and stability - Krasnopolsky, Yu. M.; Dudnichenko, А. S. (Morion LLC, 2017)
The article presents the results of developing the composition and technology of obtaining the liposomal form of docetaxel. The effect of the phospholipid composition of the membrane, ionic strength, pH, temperature, cryoprotectant type, and other factors on the stability of liposomes and the docetaxel incorporation has been considered. Results: Reduction of toxicity of the liposomal form of docetaxel (LD50 – 137 ± 7.7 mg/kg) was found in comparison with its free form (LD50 – 101 ± 6.3 mg/kg). Preservation of nanosize particle after lyophilization has been shown. Conclusions: As a result of the studies, the optimal composition and technological scheme for obtaining liposomes containing docetaxel have been developed allowing large-scale production of docetaxel in liposomal form.
Keywords: liposomes; docetaxel; liposomal drugs; toxicity